2018
DOI: 10.1093/tbm/iby113
|View full text |Cite
|
Sign up to set email alerts
|

A content analysis of smartphone apps for adolescent smoking cessation

Abstract: Adolescent cigarette smokers have an increased risk of sustained smoking into adulthood. Smartphone applications (apps) for smoking cessation are a promising treatment resource. However, research on apps for adolescent smoking cessation is limited. This study compared smoking cessation mobile apps targeting an adolescent audience with popular cessation apps for a general audience. Adolescent and general-audience apps were identified by searching the Google Play and Apple App Stores (November 2016). Two coders … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
16
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 21 publications
(16 citation statements)
references
References 25 publications
0
16
0
Order By: Relevance
“…The landscape of smoking cessation apps is rapidly changing. Currently available apps are variable in their content and features [ 27 , 29 , 55 - 58 ], and few contain content that adheres to clinical practice guidelines [ 27 , 55 - 57 , 59 - 61 ]. A recent literature review [ 29 ] found that most smoking cessation apps included self-tracking features, but only one-third included social support and one-third included rewards systems.…”
Section: Discussionmentioning
confidence: 99%
“…The landscape of smoking cessation apps is rapidly changing. Currently available apps are variable in their content and features [ 27 , 29 , 55 - 58 ], and few contain content that adheres to clinical practice guidelines [ 27 , 55 - 57 , 59 - 61 ]. A recent literature review [ 29 ] found that most smoking cessation apps included self-tracking features, but only one-third included social support and one-third included rewards systems.…”
Section: Discussionmentioning
confidence: 99%
“…Recent findings demonstrate that young adults with SMI value these and other app features, suggesting that apps may be well suited to deliver smoking cessation support to this population [12]. Although hundreds of smartphone apps are available for smoking cessation, they vary widely in their content and features [11,[13][14][15][16][17]. To our knowledge, none have been evaluated for usability, appeal, or effectiveness in young adults with SMI.…”
Section: Introductionmentioning
confidence: 99%
“…The National Cancer Institute (NCI) provides 2 smoking cessation apps based on behavioral change theories and clinical practice guidelines [11,[14][15][16]18,19]-one designed for adults (QuitGuide) and the other designed for teens (quitSTART). These apps vary considerably in their content, layout, and design.…”
Section: Introductionmentioning
confidence: 99%
“…We know that most attempts to quit smoking are not successful; according to the Centers for Disease Control and Prevention, only 12.2% of those who try to stop smoking remain abstinent [ 3 ]. For this reason, interventions that help young people and the general population stop smoking are needed.…”
Section: Discussionmentioning
confidence: 99%
“…In the case of Spain, between 80% and 90% of the population have at least one smartphone [ 1 ], which places the country at the top of European mobile phone usage, with 23 million people owning smartphones [ 2 ]. Mobile apps provide an accessible way to test new health-related methodologies, which also address user concerns around the availability and confidentiality of their personal data [ 3 ]. In Spain, users download around 4 million apps every day and, more importantly, two-thirds of teenagers (and young users) downloaded and used a mobile health app in the last year.…”
Section: Introductionmentioning
confidence: 99%